Automotive recall risk: impact of buyer-supplier relationship on supply chain social sustainability - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2019)
Purpose - The purpose of this paper is to examine the automotive product recall risk in terms of social sustainability performance and to evaluate the role of buyer-supplier relationships in improving social sustainability during product recall crises. Design/methodology/approach - A multi-methodology approach is used to empirically analyse the interrelationship between the proposed constructs and enablers of the buyer-supplier relationship. Structural equation modelling and interpretive structural modelling are followed to analyse the data gathered thorough a questionnaire survey of 204 executives and interviews with 15 managers from the automotive industry. Findings - The results of the study provide evidence regarding the impact of the responsible buyer-supplier relationship on customer recall concerns and the social sustainability performance of supply chains (SCs). This study also leads to the development of a conceptual model, providing a relationship between the three key concepts used in this study. Research limitations/implications - Following social sustainability principles, this study addresses the importance of developing strong, responsible relational ties with suppliers to reduce vehicle recalls or successfully recover from a product recall crisis. Originality/value - This study contributes to the literature by providing theoretical and empirical insights for developing socially responsible SCs and confirming the role of the buyer-supplier governance mechanism during product recalls in the context of the automotive industry.
Keywords: Sustainability; Collaboration; Business performance; Automotive industry; MULTI-TIER; CONCEPTUAL-FRAMEWORK; MANAGEMENT; PERFORMANCE; RESPONSIBILITY; BUSINESS; QUALITY; ANNOUNCEMENTS; INDICATORS; STRATEGIES